2019
DOI: 10.1177/1933719118776808
|View full text |Cite
|
Sign up to set email alerts
|

Ascites-Derived Extracellular microRNAs as Potential Biomarkers for Ovarian Cancer

Abstract: Ovarian cancer as the most fatal gynecological malignancy is often manifested by excessive fluid accumulation known as ascites or effusion. Ascites-derived microRNAs (miRNAs) may be closely associated with ovarian cancer progression. However, our knowledge of their roles, altered expression, and clinical outcomes remained limited. In this study, large-scale expression profiling of 754 human miRNAs was performed using real-time quantitative polymerase chain reaction and 384-well TaqMan array human miRNA A and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 46 publications
0
36
0
1
Order By: Relevance
“…Of these 14 highly expressed DEmiRNAs, miR-200a, miR-141, miR-1, miR-206, miR-133b, miR-133a-3p, miR-182, and miR-122 have been reported to play important roles in basic reproductive activities. miR-200a was frequently overexpressed and is closely related to the migratory, proliferative, and invasive abilities of OC cells [80][81][82]. miR-141 was shown to be significantly upregulated in OC cell lines and advanced metastatic OC [83,84], and can inhibit GC apoptosis by targeting DAPK1 through the MAPK signaling pathway, leading to the development of polycystic ovary syndrome (PCOS) [85].…”
Section: Discussionmentioning
confidence: 99%
“…Of these 14 highly expressed DEmiRNAs, miR-200a, miR-141, miR-1, miR-206, miR-133b, miR-133a-3p, miR-182, and miR-122 have been reported to play important roles in basic reproductive activities. miR-200a was frequently overexpressed and is closely related to the migratory, proliferative, and invasive abilities of OC cells [80][81][82]. miR-141 was shown to be significantly upregulated in OC cell lines and advanced metastatic OC [83,84], and can inhibit GC apoptosis by targeting DAPK1 through the MAPK signaling pathway, leading to the development of polycystic ovary syndrome (PCOS) [85].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several other studies also supported the conclusion that the expression of miR-30a was upregulated in ovarian cancer tissues (14,16). Interestingly, the study of, Wang et al (15) showed that the expression level of miR-30a in poorly differentiated ovarian papillary serous carcinoma tissues was significantly higher than that in well differentiated ovarian papillary serous carcinoma tissues.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies showed that miR-30a expression was up-regulated in the tissues of ovarian cancer (14,16). Interestingly, the study of, Wang et al (15) showed that the level of miR-30a expression in poorly differentiated ovarian papillary serous carcinoma tissues was obviously higher than that in well differentiated ovarian papillary serous carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%